Accounting for Marketing: Marketing Performance Through Financial Results - KOSAN, Levent (International Review of Management and Marketing, 2014)
Accounting, especially strategic management accounting, provides significant contributions to companies for decisions in environments of intense competition. Accounting, which has positive effects of company strategy development and management, has become a required facet of marketing, another area that has gained significance. The aim of this study is to assess the contributions of accounting to marketing performance management and other areas related to marketing development and to evaluate the relationship and synergies between marketing and accounting with comparative examples. Keywords: strategic managerial accounting; performance measurement; marketing accounting JEL Classifications: M310; M410